Interpretation and Prediction of the Hydromechanical Behavior of Unsaturated Soils from Tropical Regions - Alves, Roberto (Université d'Ottawa | University of Ottawa, 2025)
Tropical soils are widespread in many countries and regions of the world, including Brazil, large portions of the African continent, and Asia. These soils are often found in an unsaturated state and their hydromechanical behavior is predominantly influenced by their structure which is often characterized by intra and inter-aggregate pores. The intense weathering associated with high temperatures and relatively high annual rainfall results in the formation of aggregations associated with the cementation of clay particles. The top few meters of soil depth profile in tropical regions constitute a highly weathered layer (typically, lateritic soil) sitting on top of a less weathered layer with traces of the parent rock (normally, saprolitic soil). These lateritic soils attain aggregations that impart a dual-porosity resulting in a different pore size characteristics that contribute to bimodal soil-water characteristic curve (SWCC) behavior. Also, they attain different characteristics over their long formation period in comparison to conventional soils; due to this reason, traditional classification systems are not suitable. Despite advances in recent decades, there are limited studies with respect to interpretation and prediction of the hydro-mechanical behavior of bimodal lateritic soils. For this reason, there is a need for rational tools for use in conventional geotechnical engineering practice for the design of various geo-infrastructures extending the principles of unsaturated soil mechanics that are simple, especially in the context of climate change in which unprecedent changes in suction arise. Most existing constitutive models describing the behavior of unsaturated soils were developed for soils with a single pore-size family. As a result, these models have limitations or are inadequate for lateritic soils that are typically bimodal in nature. Therefore, the two major objectives of this thesis are: (i) to model the bimodal SWCC, and (ii) to model the shear strength with respect to suction for these dual porosity soils. In this context, the modeling effort includes both advances in the understanding of soil behavior and the development of prediction models. The SWCC behavior of bimodal lateritic soils was investigated by considering physicochemical aspects and their relation to the soil structure. The analyses were performed relying on a database of 27 soils divided into 25 and 15 datasets corresponding to undisturbed and remolded conditions, respectively. A new framework was proposed to estimate the bimodal SWCC for these soils based on a function describing the relation between particle and pore-size. The framework uses basic soil information and relates the macro and microstructure to the aggregated and disaggregated grain-size distribution (GSD) curves, respectively. Adsorption was indirectly considered by incorporating simple soil properties such as the liquid limit in the calibration of the function parameters. The coefficient of uniformity and the degree of aggregation were found to be associated with the desaturation zones of the macro and micropores. A simplified prediction model for the SWCC based on correlations and nonlinear regression approaches was also proposed. The regression analyses indicated that the level of aggregation and the liquid limit are the most relevant factors affecting microstructure whereas the macrostructure is strongly governed by parameters from the aggregated GSD curve. The performance of both models evaluated through R² is reasonably good, with values consistently exceeding 0.80. The shear strength model involved the analysis of the evolution of soil structure during shearing and its impact on the relationship between matric suction, net normal stress, and shear strength. Such analyses included the interpretation of the unusual behavior of some bimodal lateritic soils, where the contribution of suction to shear strength is greater than that of net normal stress (i.e., ϕb > ϕ'). The model assumes that only suctions within the micropores zone cause relevant structural changes during shearing that can decrease ϕb whereas ϕ' varies in all suction ranges. At high suctions, the contribution of suction to the shear strength becomes constant. These assumptions constitute the basis for a new shear strength prediction model that is easy to implement, requires only GSD and SWCC information, and offering superior results (R² > 0.95) in comparison to 14 unimodal and 2 bimodal models available in the literature. The increase in the effective friction angle, ϕ' with respect to matric suction during shearing seems to be a function of the level of aggregation; however, the values of the friction angle associated with matric suction, ϕb, greater than ϕ' are believed to occur due to the emergence of a contractive shear band in specimens with suctions higher than the first air-entry value in drained conditions. The relationship between apparent cohesion and matric suction appears to exhibit a linear relationship extending from saturation to the end of the macropores region, and a non-linear relationship starting from the preceding limit to the midpoint of the micropores transition region. Although the purpose of the models presented in this thesis is not to replace direct determinations using laboratory tests, they can be considered a step forward in the implementation of unsaturated soil mechanics for lateritic soils because they offer reasonable estimates of the SWCC and the unsaturated shear strength. This information is essential in developing preliminary geotechnical designs, such as those related to slope stability, retaining walls, bearing capacity of formation layers of roads and railroads, bearing capacity in foundations, cover and capillary barrier systems, and mining waste disposal systems.
Keywords: soil-water characteristic curve; unsaturated shear strength; pedotransfer functions; prediction models; lateritic soils; bimodal structure